A Balanced Scorecard for Maple Leaf Consulting. (December 2013) - Ogata, Ken; Spraakman, Gary
Abstract Maple Leaf Consulting is the disguised name for an actual medium‐sized international engineering and environmental consulting firm. In its 35 years of operations, the firm has grown from a single 10‐person office in Canada to more than 3, 000 employees worldwide. Despite the growth from providing only specialized geotechnical engineering to many related technical specializations, the firm retained its nonbureaucratic orientation. Now, while emphasizing innovative world‐class technical knowledge, the fictional firm must resolve a series of organizational transition issues, which the actual firm did through the use of the balanced scorecard. The purpose of this case is for students to develop a preliminary balanced scorecard with appropriate measures.